Changes in passively‐sensitized basophil activation to αS1‐casein after oral immunotherapy. Issue 2 (3rd March 2020) - Matsui, Teruaki; Naito, Michihiro; Tagami, Kazunori; Tajima, Iwao; Teshigawara, Miyuki; Makino, Atsushi; Kitamura, Katsumasa; Takasato, Yoshihiro; Sugiura, Shiro; Yamada, Chikako; Izumi, Hidehiko; Tsuge, Ikuya; et al.
Abstract: Introduction: Immune response to cow's milk allergen (CMA) has been analyzed mostly using crude milk antigen or a mixture of various caseins. This study aimed to assess the changes in the immunological response against αS1‐casein during oral immunotherapy (OIT) and to investigate the mechanism of tolerance. Methods: We have performed rush OIT to 39 patients with CMA and obtained the serum samples up to 3 years after OIT. Immunoglobulin E (IgE) and IgG4 antibodies specific to highly purified αS1‐casein as well as passively‐sensitized basophil activation were evaluated using the serial samples. Furthermore, we examined whether basophil activation led by the pre‐OIT serum was suppressed by the post‐OIT serum, or by the tolerant serum obtained from naturally outgrown patients. Results: Specific IgE to αS1‐casein was significantly reduced after OIT. Specific IgG4 (sIgG4) to αS1‐casein was also detected in most of the pre‐OIT sera, which was not significantly increased after OIT. Activation of passively‐sensitized basophils to αS1‐casein was significantly reduced after 2 years (14% ± 19%) and 3 years (19% ± 18%) post‐OIT compared with pre‐OIT (%CD63 high basophils; 51% ± 27%). Furthermore, the addition of post‐OIT or tolerant serum to pre‐OIT serum significantly suppressed the basophil activation. This suppression was abrogated by washing the supernatant after passive sensitization, but not by depleting IgG antibodies from post‐OIT or tolerant sera, nor by blocking FcγRIIb using an anti‐FcγR antibody. Conclusions: αS1‐casein‐sIgG4 plays a minor role in tolerance mechanisms in cases of CMA; humoral factors other than antigen‐sIgG4 may be involved. Abstract : Cow's milk oral immunotherapy (OIT) led to an increased tolerated amount of cow's milk. While αS1‐casein‐specific immunoglobulin E decreased and basophil activation stimulated by αS1‐casein was reduced, αS1‐casein‐specific IgG4 did not increase. Antigen‐specific humoral factors other than IgG4 both in post‐OIT and sera of patients with the natural outgrowth of cow's milk allergy could inhibit basophil activation sensitized by pre‐OIT sera.